THE APPROACH OF SOCIAL MARKETING OF THE HIGHER EDUCATION INSTITUTION OF PHYSICAL CULTURE AND SPORT BASED ON IMAGE - Liliana BUDEVICI - PUIU; Ecaterina AMELICICHIN (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
The assessment of students, clients, bachelors, beneficiaries, the auxiliary teaching and non-teaching staff regarding some important aspects related to the activity and duties of the Academic Institution of Physical Education and Sport (reflects the study on a Institutional level) are very important on making a social image of prosperity Thus, the media, social marketing are effective tools in promoting the image of the higher education institution of physical culture and sport. Also the information of marketing's research can have a significantly role in direction of Academic Institution activity towards the improvement of its educational services for students' benefit and potential beneficiaries.